Pengaruh Musaqah terhadap tingkat Kesejahteraan Petani Kelapa - Nursupiana Rastini; Hendro Lisa; Selviani Selviani (AL-Muqayyad, 2021)
The purpose of this study was to determine the effect, significance value and percentage of musaqah on the welfare level of coconut farmers, especially coconut farmers.This type of research is quantitative research, namely analyzing in the form of data in the form of numbers. Sampling with random sampling technique.The results of this study indicate that the t-count value is 4.229 so that the t-table is 1.972 < t-count is 4.229 with a significance of 0.000 <0.005. Thus, it can be concluded that musaqah influences the level of welfare of coconut farmers and has a significant effect. The percentage of musaqah influence on the welfare level of coconut farmers is 25.3%, while the remaining 74.7% is influenced by other variables not included in this study